Performance Management System Design Based on Balanced Scorecard in PT Krakatau Tirta Industri - Sulistyo, Iwan; Basri, Mursyid Hasan (The Indonesian Journal of Business Administration, 2013)
The business environment is growing very fast including water business. Investment in clean water becomes more open to private national and foreign. Technology developments in the field of clean water grow fast both in terms of water quality and efficiency so the competitions become very important issue.Â  The company wants its business remains sustainable so it not just focuses on the financial performance but also focus to all aspects affecting the long-term business viability. This problem can be solved by using a framework that can align the business situation, the company's vision, strategy and operational objectives also monitor the realization. One framework that can meet the needs is the balanced scorecard (BSC). BSC consists of four perspectives: financial perspective, customer perspective, internal process perspective and learning and growth perspectives. Research has been done in this final project resulted performance management system design based on the balanced scorecard in PT. Krakatau Tirta Industri. Application of BSC is focused on achieving sustainable financial growth with emphasis to the completion of the raw water shortage problems and business development. Execution is the key step that PT. KTI has an objective goal to encourage employees to have high productivity in their strategy map. Strategy map than deployed to the division level that all available resources are used to achieve the targets set in order to achieve the company's vision as a world class water supply company. Application BSC is expected to support the achievement of the company's vision to provide good value to consumers; businesses develop and improve internal processes become more efficient and effective, workforce competency development as demanded changes, effective organization and good organizational culture. Application of balanced scorecard requires commitment and participation of all parties, especially top management. Monitoring and evaluation should be carried out periodically by top management in order to produce feedback to achieve its targets. Â Keywords: Performance management system, balanced scorecard, feedback.Â